Study of Tapered Threads Parameters Affecting the Quality of the Oil Pipeline Connection - I. K. Tsybrii; N. S. Koval; Zh. N. Issabekov (Advanced Engineering Research, 2022)
Introduction. With the growth in the production and transportation of gas and oil, the urgency of the problem of tightness of the connection of pipes of the oil and gas range increases. The most common are coupling and streamline threaded connections. Threads of the buttress type, conical trapezoidal, and triangular threads are used. The tightness of the connection depends directly on their quality. The production of pipes and couplings is influenced by many factors. Examples include technological heredity, rigidity of technological equipment, its setting and resetting. The required connection quality is provided by the quality of the elements. The assembly should take into account the possibility of complete interchangeability. The second recommended option is a group assembling. In all cases, control operations are mandatory. The paper presents the results of studies on the distribution of pipe and coupling thread quality parameters in the batch.Materials and Methods. Fragments (tubular parts) of casing pipes with trapezoidal thread and increased tightness (CPTT) and with trapezoidal thread of the buttress profile were studied. They were randomly selected from different batches. When measuring, the samples were fixed in the chuck of 1I611P lathe. The measuring instrument was a clock type 0 accuracy class indicator with a stand. Generally accepted statistical methods were used to evaluate the data obtained.Results. The experiments have found how the tightness of the connection through the method of complete interchangeability is affected by the radial runout of the surfaces of the thread profile tops, the pipe chamfers, and the sealing belt.Discussion and Conclusions. Significant deviations of the values of the thread parameters from the permissible ones were found, which might cause a leak in the connection. Obtaining a high-quality and reliable connection is possible when assembling by the method of incomplete or group interchangeability.